STUDENT-CENTERED AND INTERACTIVE TEACHING IN MEDICAL UNIVERSITIES - Raxmonova Feruza,; Maksudova Malika,; Nadirova Yulduz, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract In recent years, medical education has undergone significant transformation due to  rapid  advancements  in  science,  technology,  and  healthcare  systems.  Traditional teacher-centered  instructional  models  are  increasingly  being  replaced  by  student-centered and interactive teaching approaches that emphasize active learning, critical thinking,  and  practical  competence.  This  article  examines  the  concept  of  student-centered  and  interactive  teaching  in  medical  universities,  explores  commonly  used interactive methods, and analyzes their impact on students’ academic performance, clinical skills, and professional development. The study highlights the importance of implementing  innovative  pedagogical  strategies  to  improve  the  quality  of  medical education and better prepare future healthcare professionals for real-world challenges.